1970
DOI: 10.3126/narj.v7i0.1864
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Harvesting Method and Calcium on Post Harvest Physiology of Tomato

Abstract: An experiment was conducted in Institute of Agriculture and Animal Science, Rampur, Chitwanduring 2003 to find out the effect of harvesting method and calcium chloride treatment on postharvestphysiology of tomato. Tomato (Hybrid Gootya) fruits with stalk and without stalk wereharvested at breaker stage and dipped in distilled water and different concentrations of calciumchloride viz. 0.25%, 0.50%, 0.75% and 1% for fifteen minutes. Fruit were then air-dried andstored at ambient condition (24 ± 3°C and 70 ± 5 % … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
34
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(39 citation statements)
references
References 3 publications
5
34
0
Order By: Relevance
“…Agar and Kaska (1995) also reported similar results. The experiment conducted by Bhattarai and Gautam (2006) had also the similar type of results. …”
Section: Shelf-life and Tsssupporting
confidence: 68%
“…Agar and Kaska (1995) also reported similar results. The experiment conducted by Bhattarai and Gautam (2006) had also the similar type of results. …”
Section: Shelf-life and Tsssupporting
confidence: 68%
“…Also, fruits treated with CaCl 2 have been shown to have reduced physiological weight loss and maintain higher firmness levels during storage [81]. Bhattarai and Gautam [82] also reported a reduction of physiological weight loss in tomatoes from 19% to 17% by using 0.25% CaCl 2 application for 10-day storage. However, CaCl 2 is a very cheap and soluble salt which can be dissolved into any concentration for use by producers.…”
Section: -Methylcyclopropene (1-mcp)mentioning
confidence: 93%
“…Bhattarai and Gautam (2006) reported that during storage the fruit itself might utilize acids and hence the acid content in fruit decreases with prolonged storage. The Regression Coefficient table for RSM analysis for Titrable Acidity as response variable is shown in Table 3.…”
Section: Hernandezmentioning
confidence: 99%